Loss of Primary Cilia Protein IFT20 Dysregulates Lymphatic Vessel Patterning in Development and Inflammation - Paulson, Delayna; Harms, Rebecca; Ward, Cody; Latterell, Mackenzie; Pazour, Gregory J.; Fink, Darci M. (Frontiers in Cell and Developmental Biology, 2021)
Microenvironmental signals produced during development or inflammation stimulate lymphatic endothelial cells to undergo lymphangiogenesis, in which they sprout, proliferate, and migrate to expand the vascular network. Many cell types detect changes in extracellular conditions via primary cilia, microtubule-based cellular protrusions that house specialized membrane receptors and signaling complexes. Primary cilia are critical for receipt of extracellular cues from both ligand-receptor pathways and physical forces such as fluid shear stress. Here, we report the presence of primary cilia on immortalized mouse and primary adult human dermal lymphatic endothelial cells in vitro and on both luminal and abluminal domains of mouse corneal, skin, and mesenteric lymphatic vessels in vivo. The purpose of this study was to determine the effects of disrupting primary cilia on lymphatic vessel patterning during development and inflammation. Intraflagellar transport protein 20 (IFT20) is part of the transport machinery required for ciliary assembly and function. To disrupt primary ciliary signaling, we generated global and lymphatic endothelium-specific IFT20 knockout mouse models and used immunofluorescence microscopy to quantify changes in lymphatic vessel patterning at E16.5 and in adult suture-mediated corneal lymphangiogenesis. Loss of IFT20 during development resulted in edema, increased and more variable lymphatic vessel caliber and branching, as well as red blood cell-filled lymphatics. We used a corneal suture model to determine ciliation status of lymphatic vessels during acute, recurrent, and tumor-associated inflammatory reactions and wound healing. Primary cilia were present on corneal lymphatics during all of the mechanistically distinct lymphatic patterning events of the model and assembled on lymphatic endothelial cells residing at the limbus, stalk, and vessel tip. Lymphatic-specific deletion of IFT20 cell-autonomously exacerbated acute corneal lymphangiogenesis resulting in increased lymphatic vessel density and branching. These data are the first functional studies of primary cilia on lymphatic endothelial cells and reveal a new dimension in regulation of lymphatic vascular biology.